DIAGNOSTIC AND TREATMENT APPROACHES FOR ACUTE INTESTINAL OBSTRUCTION IN THE EARLY POSTPARTUM PERIOD - Mishchenko, V.V.; Mishchenko, V.P.; Nikitenko, R.P.; Vorotyntseva, K.O.; Degtyarenko, S.P.; Koychev, E.A.; Likhachov, V.K. (World of Medicine and Biology, 2023)
Acute intestinal obstruction is one of the most serious acute surgical diseases of the abdominal organs in the early postpartum period. 31 women in labor with acute intestinal obstruction were treated. The Algorithm of therapeutic and diagnostic tactics in parturient women with acute intestinal obstruction was developed and proposed for use. The indication for surgery was the lack of effect of conservative therapy within 2–3 hours. Surgical treatment was performed in all cases of acute mechanical obstruction. Conservative measures had a positive effect in all women in labor of the dynamic intestinal obstruction. No fatalities were registered. Treatment of women in labor with acute intestinal obstruction should be carried out by surgeons with the involvement of obstetrician–gynecologists in accordance with the proposed algorithm of treatment and diagnostic tactics in women in labor with acute intestinal obstruction.